STRATEGIC PERSPECTIVE: USTU AS A CENTER OF INNOVATIVE, TECHNOLOGICAL, AND SOCIAL DEVELOPMENT OF THE KOMI REPUBLIC - N. D. Tskhadaya (Высшее образование в России)
The article reveals the potential of the Ukhta State Technical University as a center of innovative technological and social development of the region. The authors shows how the university has been converted in an operational model of innovation economy. The university structure includes the university complex, technopark, and territorial cluster.